PENINGKATAN KEMAMPUAN TEKNIK DASAR FOREHAND PERMAINAN TENIS MEJA DENGAN METODE LATIHAN TERBIMBING MATA PELAJARAN PENJASKESDIKELAS XII IPA 3 SMA NEGERI 3 TEBING TINGGI - Bahrum Bahrum (PGSD Universitas Negeri Medan, 2016)
This purpose of this research is to improving forehand hit in table tennis through guided exercises method. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class XII IPA 3 Senior High School State 3 Tebing Tinggi which amounted to 37 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the guided exercise method can improve forehand hitin table tennis, characterized by increased mastery learning students, namely pre-cycle (54,5%), the first cycle (72,97%), cycle II (86,48%) and complete learn the clasical equal to 86,48 %.Key Word :Guided exercise,table tennis, forehand